A root‐knot nematode small glycine and cysteine‐rich secreted effector, MiSGCR1, is involved in plant parasitism. Issue 2 (16th October 2017) - Nguyen, Chinh‐Nghia; Perfus‐Barbeoch, Laetitia; Quentin, Michaël; Zhao, Jianlong; Magliano, Marc; Marteu, Nathalie; Da Rocha, Martine; Nottet, Nicolas; Abad, Pierre; Favery, Bruno
Summary: Root‐knot nematodes, Meloidogyne spp., are obligate endoparasites that maintain a biotrophic relationship with their hosts. They infect roots as microscopic vermiform second‐stage juveniles, and establish specialized feeding structures called 'giant‐cells', from which they withdraw water and nutrients. The nematode effector proteins secreted in planta are key elements in the molecular dialogue of parasitism. Here, we compared Illumina RNA‐seq transcriptomes for M. incognita obtained at various points in the lifecycle, and identified 31 genes more strongly expressed in parasitic stages than in preparasitic juveniles. We then selected candidate effectors for functional characterization. Quantitative real‐time PCR and in situ hybridizations showed that the validated differentially expressed genes are predominantly specifically expressed in oesophageal glands of the nematode. We also soaked the nematodes in siRNA to silence these genes and to determine their role in pathogenicity. The silencing of the dorsal gland specific‐ Minc18876 and its paralogues resulted in a significant, reproducible decrease in the number of mature females with egg masses, demonstrating a potentially important role for the small glycine‐ and cysteine‐rich effector MiSGCR1 in early stages of plant‐nematode interaction. Finally, we report that MiSGCR1 suppresses plant cell death induced by bacterial or oomycete triggers of plant defense.